Barriers, Attitudes, and Influences Towards Dietary Intake Amongst Elite Rugby Union Players - Sharples, A. M.; Galloway, Stuart D.; Baker, D.; Smith, Brett; Black, Katherine (Frontiers in Sports and Active Living, 2021)
Background: Dietary intakes can impact an athletes health and performance, although evidence exists about what an athlete should eat, an athlete’s nutritional intake is influenced by many factors. The limited research available suggests the main barriers preventing optimal nutritional intakes reported by athletes are lack of time, food accessibility, poor cooking skills, costs, taste and time spent in ‘off-season’. Although these factors have been shown to influence dietary intake they remain relatively unexplored in male Rugby Union. This study aimed to describe the barriers and nutritional influences on dietary intake amongst Male Rugby Union player’s. Methods: This was a qualitative study utilising in person individual interviews with all participants. Participants were Rugby Union players (n=30) for either a Super Rugby franchise or one of their development squads in New Zealand were recruited for this study. Participant’s undertook recorded face to face interviews, which were recorded and later transcribed. A thematic approach was used to code the transcripts by the primary coder and the themes were subsequently evaluated by the research team. Results: Childhood upbringing, organisational skills, time and food security also emerged as barriers. Body composition and sport nutrition knowledge emerged as both barriers and enablers to nutritional intake. Influence on performance was an enabler to optimal dietary intake. Fully professional rugby players have daily access to nutritionists/dietitians, whereas development and semi-professional rugby players only have limited access, they were more likely to seek nutritional information via social media. Conclusion: This study suggests a need for greater nutrition education at developmental levels with an emphasis on affordable food choices, meal planning and skills for interpreting online nutrition information.